Clinical Validation of a Transcranial Doppler-Based Noninvasive Intracranial Pressure Meter: A Prospective Cross-Sectional Study - Bershad, Eric M.; Anand, Aashish; DeSantis, Stacia M.; Yang, Ming; Tang, Rosa A.; Calvillo, Eusebia; Malkin-Gosdin, Leslie; Foroozan, Rod; Damani, Rahul; Maldonado, Nelson; Gupta, Pramod; Tan, Benedict; et al. (World neurosurgery, 2016)
Noninvasive intracranial pressure (ICP) measurement would represent a major advance for patients with neurological problems. The Vittamed ICP meter is an ultrasound-based device reported to have high agreement with lumbar puncture cerebrospinal fluid (CSF) pressure measurement. However, previous studies included mostly patients with normal levels of ICP. The purpose of our study was to perform an independent clinical validation study of a transcranial Doppler-based noninvasive ICP meter in patients anticipated to have a wide range of ICP. In a prospective cross-sectional design, we simultaneously measured ICP with the Vittamed device and the invasive lumbar CSF pressure. The operator of each procedure was blinded to the result of the other method. Data were analyzed using Bland-Altman plots, Pearson correlation coefficients, and receiver operator characteristic curves. Twenty-four independent paired measurements of Vittamed and lumbar CSF pressure were obtained; with mean absolute difference between paired measures of 4.5 mmHg (standard deviation 3.1). The 95% limits of agreement were −10.5 to +11.0. The systematic bias (mean of paired differences) was negligible at 0.25 mmHg. The sensitivity, specificity, and area under the curve for ICP >20 mmHg were 0.73, 0.77, and 0.71, respectively. The Vittamed ICP meter had fair agreement with lumbar CSF pressure measurement. The wide limits of agreement would preclude using this version of the device as a stand-alone method for ICP determination, but may be useful if combined with other ICP screening methods. Ongoing improvements to the Vittamed hardware and software may lead to improvements in accuracy and clinical utility of this device.